Resistance to Intergroup Helping: The Effects of Motive and Audience from the Perspective of Observer Group - Mashuri, Ali; Nuryanti, Sofia (Universitas Islam Indonesia, 2024)
Help provision, often perceived as an act of kindness, is often resisted or rejected by the recipients. Preliminary research examined the resistance showed by help recipients, with none conducted on the resistance perceived by observer groups. Therefore, this research aimed to examine the effect of motives (prosocial versus strategic) and audience (private versus public) on resistance to intergroup helping through the perspective of observer. Data were collected from 1,752 participants recruited using the convenient sampling method. The first hypotheses showed that the motives with values of B = .30, t = 7.66, p < .001, and the audience comprising B = .46, t = 11.66, p < .001, significantly resulted in higher levels of observer positive evaluations of intergroup helping. The second hypothesis showed that observer positive evaluations of intergroup helping significantly decreased observer resistance to intergroup helping, B = -.28, t = -10.40, p < .001. The third hypothesis showed that the positive evaluation of intergroup help significantly mediated the effect of prosocial motives (indirect effect: B = -.09, the lower limit of the confidence interval [LLCI] = -.11, upper limit of the confidence interval [ULCI] = -.06) and private audiences (indirect effect: B = -.13, LLCI = -.16, ULCI = -.10) in reducing observer resistance to intergroup help. These empirical results collectively emphasized the significance of a group reputation or image in extending help to others, influencing the perspective of observer regarding accepting or rejecting intergroup aid.